INTRODUCING A NEW CONCEPT IN DENTISTS'CURRICULA: MANAGEMENT OF NICOTINE DEPENDENCE IN SMOKERS WITH ORAL DISEASES - Antigona TROFOR; Valentina ESANU; Ramona MIRON; Letitia TROFOR (Romanian Dental Association for Education, 2013)
Most people are now aware that smoking is bad for health. It can cause many different medical problems and, in some cases, fatal diseases. However, many people don't realize the damage that smoking does to their mouth, gums and teeth. Smoking can lead to tooth staining, gum disease, tooth loss bad breath, enable efficiency of periodontal treatment or dental implants and induces oral cancer.As for any other disease, diagnosis of tobacco use must be followed by treatment, which is entitled advice/counselling to quit smoking and has two major components: pharmacological methods and cognitive-behavioural approach, optionally adding psychotherapy, hypnosis, self-helping written materials, support qui lines. Quitting smoking is a difficult process, as nicotine dependence is difficult to treat. Only 3-5% of smokers achieve tobacco use abstinence based on own will; majority of the cases need expert medical advice, therapy and counselling For this purpose, this paper is giving some basic landmarks to help improving quality of medical services delivered by dentists to this category of patients.